Practitioner Profile: An Interview with Erin Wirth, AFC - Erin Wirth (Journal of Financial Therapy, 2013)
Erin Wirth is an Accredited Financial Counselor and the Director of the University of Nebraska – Lincoln Student Money Management Center, a financial education program for college students. The program offers one-on-one money management education and counseling sessions, money management workshops, and a variety of other interactive educational activities aimed to help college students understand the importance of financial literacy. The program recently won the Outstanding Financial Counseling & Planning Education Award from the Association for Financial Counseling & Planning Education.
Keywords: financial counseling; financial therapy